Methylation levels of the TNFA gene are different between Graves' and Hashimoto's diseases and influenced by the TNFA polymorphism. (3rd April 2018) - Morita, Emi; Watanabe, Mikio; Inoue, Naoya; Hashimoto, Hidemi; Haga, Emi; Hidaka, Yoh; Iwatani, Yoshinori
Abstract: Graves' disease (GD) and Hashimoto's disease (HD) are different pathological types of autoimmune thyroid diseases (AITDs). However, the epigenetic differences between these diseases have not been elucidated. DNA methylation is one of the primary epigenetic modifications that reflect environmental influences on gene expression. In this study, we evaluated the methylation status of six CpG sites in the TNFA promoter using pyrosequencing and analyzed the data in combination with functional polymorphisms (−1031 T/C and +123 C/T) in the TNFA gene to clarify the role of gene methylation on the prognosis of AITDs. We examined the methylation pattern in 52 patients with GD, 60 patients with HD, and 29 healthy controls by pyrosequencing. Additionally, we also genotyped the polymorphisms from 163 patients with GD, 152 patients with HD, and 94 healthy controls using the restriction fragment length polymorphism (RFLP) method. Each proportion of subjects with low methylation of the −72 CpG site (≤11.9%), low methylation of the −49 CpG site (≤15.5%), and low methylation of the −38 CpG site (≤8.9%) was significantly increased in the groups with high concentration of TNF-α (≥0.134 pg/mL). The methylation level of the −72 CpG site was significantly higher in GD cases (10.7 ± 4.9%) than in healthy controls (6.8 ± 3.9%). The methylation level of the −49 and −38 CpG sites were significantly higher in patients with GD in remission (20.5 ± 9.5%, 17.6 ± 8.0%, respectively) than in healthy controls (13.0 ± 7.6%, 7.9 ± 7.3%, respectively). The frequency of the TNFA − 1031C carrier (CT + CC) is correlated with higher TNF-α production and was significantly higher in GD (35.0%) and HD (39.5%) cases than in controls (19.1%). In the subjects with the TNFA − 1031C carrier (CT + CC), the methylation level of the −72 CpG site was significantly higher in GD (11.5 ± 5.7%) than in HD (6.0 ± 3.4%). However, there was no difference between GD and HD in patients with the TT genotype. Cumulatively, our data indicate the methylation levels of CpG sites in the TNFA gene may be related to the difference between GD and HD in AITDs and may be influenced by the TNFA gene polymorphism.